2021
DOI: 10.1007/s00281-021-00836-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine “fine tuning” of enthesis tissue homeostasis as a pointer to spondyloarthritis pathogenesis with a focus on relevant TNF and IL-17 targeted therapies

Abstract: A curious feature of axial disease in ankylosing spondylitis (AS) and related non-radiographic axial spondyloarthropathy (nrAxSpA) is that spinal inflammation may ultimately be associated with excessive entheseal tissue repair with new bone formation. Other SpA associated target tissues including the gut and the skin have well established paradigms on how local tissue immune responses and proven disease relevant cytokines including TNF and the IL-23/17 axis contribute to tissue repair. Normal skeletal homeosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 149 publications
(186 reference statements)
1
14
0
2
Order By: Relevance
“…We also found that this IL-23 secretion could be attenuated by the addition of PDE4 blockers which may be relevant translationally since antagonism of this pathway shows efficacy for peripheral enthesitis in PsA in man (56). Both TNF and IL-17A are able to also induce osteogenesis in vitro in MSC from the spinal enthesis (60,61).…”
Section: Emerging Immunology Of the Il-23 Pathway And Il-23/17 Axis Imentioning
confidence: 61%
“…We also found that this IL-23 secretion could be attenuated by the addition of PDE4 blockers which may be relevant translationally since antagonism of this pathway shows efficacy for peripheral enthesitis in PsA in man (56). Both TNF and IL-17A are able to also induce osteogenesis in vitro in MSC from the spinal enthesis (60,61).…”
Section: Emerging Immunology Of the Il-23 Pathway And Il-23/17 Axis Imentioning
confidence: 61%
“…Zudem stellten wir fest, dass sich diese IL-23-Sekretion durch die Gabe von Phosphodiesterase-4 (PDE4)-Blockern abschwächen ließ, was translational bedeutsam sein könnte, da die Antagonisierung dieses Signalwegs beim Menschen Wirksamkeit bei peripherer Enthesitis bei PsA zeigt [56]. Sowohl TNF als auch IL-17A sind in der Lage, die Osteogenese in vitro in mesenchymalen Stammzellen (mesenchymal stem cells, MSCs) aus der spinalen Enthese zu induzieren [60, 61].…”
Section: Neu Aufkommende Immunologische Erkenntnisse Zum Il-23-signalweg Und Der Il-23/17-achse Bei Spa Beim Menschenunclassified
“…This clinical heterogeneity is reflected in complex pathophysiology, knowledge of which is crucial to hypothesizing a therapeutic approach targeting the ongoing pathological process ( Veale and Fearon, 2018 ; Scher et al, 2019 ; Russell et al, 2021 ). Infiltration of both innate and adaptive immune cells in different target organs and tissues results in significant production of different proinflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, IL-22, IL-23, IL-17A, and IL-18, inducing further inflammatory mediators release and damage progression.…”
Section: Introductionmentioning
confidence: 99%